The integration of augmented reality innovation in lip matte combo packaging / Mohamad Izzat Jamel - Jamel, Mohamad Izzat (Universiti Teknologi MARA, Perak, 2022)
In the early days, a generic, plain – looking box packaging is quite common and boring to look at. However, to date, the design of packaging itself should be able to support the product inside while looking aesthetically pleasing to the eyes to attract customers purchase. Packaging could be defined as the process of enclosing products made using any materials that are able to contain, protect, handle, deliver and preserve goods from the manufacturer to consumers.